“Genuine Brotherhood” without Remorse: A Commentary on Joseph Ratzinger’s "Comments on 'De Iudaeis'" - Cunningham, Philip A.; Gregerman, Adam (Studies in Christian-Jewish Relations, 2019)
This article critically engages, section by section, a 2018 essay on Catholic-Jewish relations by emeritus Pope Benedict XVI. It is the result of joint analysis by a Jewish professor and a Catholic professor who co-direct an academic institute devoted to Catholic-Jewish relations. Benedict’s treatment of such topics as supersessionism, the “unrevoked covenant,” and the State of Israel is complex, and his reasoning is often difficult to follow, but the authors conclude that his essay makes genuine contributions to a Catholic theology of relations with Jews and Judaism that deserve serious, dispassionate, and critical study. This is true despite some serious weaknesses, especially its lack of consistent engagement with Judaism as lived by Jews today.